2009
DOI: 10.3748/wjg.15.2277
|View full text |Cite
|
Sign up to set email alerts
|

Jejunoileal bypass: A surgery of the past and a review of its complications

Abstract: Jejunoileal bypass (JIB), popular in the 1960s and 1970s, had remarkable success in achieving weight loss by creating a surgical short bowel syndrome. Our patient had an unusual case of liver disease and provided no history of prior bariatric surgery. Later, it was recognized that he had a JIB in the 1970s, which was also responsible for the gamut of his illnesses. Patients with JIB are often not recognized, as they died of complications, or underwent reversal of their surgery or a liver-kidney transplant. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 6 publications
0
35
0
6
Order By: Relevance
“…Although the data on the risk of kidney stones following mixed restrictive and malabsorptive procedures causing significant malabsorption such as very-long limb RYGB or biliopancreatic diversion with duodenal switch were limited, it has already been well established that these procedure can cause fat malabsorption which can lead to enteric hyperoxaluria and calcium oxalate stone formation. [10][11][12]15 Recently, the findings from a population-based study by Lieske et al 15 reported an increased risk of kidney stones in patients following Figure 2. Forest plot of the all included studies comparing risk of kidney stones in patients who underwent bariatric surgery and those who did not; square data markers represent risk ratios (RRs); horizontal lines, the 95% CIs with marker size reflecting the statistical weight of the study using random-effects meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the data on the risk of kidney stones following mixed restrictive and malabsorptive procedures causing significant malabsorption such as very-long limb RYGB or biliopancreatic diversion with duodenal switch were limited, it has already been well established that these procedure can cause fat malabsorption which can lead to enteric hyperoxaluria and calcium oxalate stone formation. [10][11][12]15 Recently, the findings from a population-based study by Lieske et al 15 reported an increased risk of kidney stones in patients following Figure 2. Forest plot of the all included studies comparing risk of kidney stones in patients who underwent bariatric surgery and those who did not; square data markers represent risk ratios (RRs); horizontal lines, the 95% CIs with marker size reflecting the statistical weight of the study using random-effects meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite lack of controls, studies have identified kidney stones as a well-known complication of purely malabsorptive bariatric procedures, such as Jejunoileal bypass. [10][11][12] However, the findings of studies evaluating the risk of kidney stones in patients following modern bariatric surgery are conflicting. 13 Several studies have demonstrated an increased risk of kidney stones in patients following bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…26 Jejuno ileal bypass is not used anymore because of numerous and sometimes severe side effects, such as protein malnutrition, vitamin and mineral deficiencies, renal failure, liver disease, and even death. 27 However, information derived from the changes in gastrointestinal hormones after JIB can be applied to increase knowledge about how currently used bariatric surgery operations work.…”
Section: Gastric Restrictive (Laparoscopic Adjustable Gastric Bandingmentioning
confidence: 99%
“…Jejunoileal by-pass uygulanan hastalarda operasyondan 15 yıl sonra böbrek taşı görülme riski yaklaşık %29'dur [18,19]. Obezite cerrahisi sonrası oluşan taşlar ço-ğunlukla kalsiyum okzalat taşıdır.…”
Section: Obezite Cerrahisi Ve üRiner Sistem Taşı Oluşumuunclassified